Cloud-Based Mobile App Testing Framework: Architecture, Implementation and Execution - Rojas, Isabel K. Villanes; Meireles, Silvia; Dias-Neto, Arilo Claudio (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2016: Anais do I Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2016)
The growth in the use of mobile devices is notorious due to the multiple functionalities they offer. The time between the release of new device models and mobile platform updates is very short, and this has a direct influence on the quality of mobile applications, because these applications need to be compatible with new mobile devices and the different versions of mobile platforms. As a negative consequence, the quality of mobile apps would be lower than expected. Therefore, to ensure mobile application quality, many services for mobile test are offered as Cloud Testing. Thus, this work proposes a Mobile Cloud Testing Framework, called AM-TaaS, that meets these needs. AM-TaaS facilitates the test environment setup and configuration and covers a range of mobile devices and platforms. We also describe the architecture and implementation of the proposed framework. With the use of AM-TaaS framework, it is possible to perform mobile app testing on different mobile emulators/devices.